Performance of Silicon carbide whisker reinforced ceramic inserts on Inconel 718 in end milling process - Moola, Mohan; Joshua, C. (2016)
An experimental investigation is planned in order to study the machinability of Inconel 718 with silicon carbide whisker reinforced ceramic inserts in end milling process. The relationship between the cutting speed, feed rate, and depth of cut against the response factors are studied to show the level of significance of each parameter. The cutting parameters are optimized by using Taguchi method. Implementing analysis of variance, the parameter which influences the surface roughness the most is determined to be the cutting speed, followed by the feed rate and depth of cut. Meanwhile, the optimal cutting condition is determined to have high cutting speed, low feed rate, and high depth of cut in the range of selected parameters.